2012
DOI: 10.1523/jneurosci.1253-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor-Dependent Synaptic Plasticity Is Suppressed by Interleukin-1β via p38 Mitogen-Activated Protein Kinase

Abstract: Evolving evidence suggests that brain inflammation and the buildup of proinflammatory cytokines increases the risk for cognitive decline and cognitive dysfunction. Interleukin-1β (IL-1β), acting via poorly understood mechanisms, appears to be a key cytokine in causing these deleterious effects along with a presumably related loss of LTP-type synaptic plasticity. We hypothesized that IL-1β disrupts BDNF signaling cascades and thereby impairs the formation of filamentous actin (F-actin) in dendritic spines, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(202 citation statements)
references
References 68 publications
(114 reference statements)
16
185
0
1
Order By: Relevance
“…The effect we found on episodic memory is in line with a broad scientific literature that indicates that p38 α in involved in oligomeric amyloid‐beta and inflammation‐induced synaptic dysfunction and to stress‐ and age‐related synaptic dysfunction in the hippocampus 4, 5, 10, 11, 12, 13, 14, 31. In our clinical study, the ES that we saw for immediate and delay recall compares favorably to ES of ≤0.2 for WMS immediate or delayed recall at week 12 in the placebo‐treated subjects in two trials of Souvenaid in a similar patient population (mild AD, baseline MMSE = 24) 32, 33.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The effect we found on episodic memory is in line with a broad scientific literature that indicates that p38 α in involved in oligomeric amyloid‐beta and inflammation‐induced synaptic dysfunction and to stress‐ and age‐related synaptic dysfunction in the hippocampus 4, 5, 10, 11, 12, 13, 14, 31. In our clinical study, the ES that we saw for immediate and delay recall compares favorably to ES of ≤0.2 for WMS immediate or delayed recall at week 12 in the placebo‐treated subjects in two trials of Souvenaid in a similar patient population (mild AD, baseline MMSE = 24) 32, 33.…”
Section: Discussionsupporting
confidence: 90%
“…Traditionally p38 α kinase is considered to be an inflammation‐related target as microglial p38 α promotes production of proinflammatory cytokines6 and modulates microglial activation state,7, 8 and in the healthy state p38 α expression within neurons is low 9. However, more recent findings indicate that neuronal p38 α is increased in disease and under stress, and neuronal p38 α expression has been implicated in amyloid‐beta and/or inflammation‐induced synaptic dysfunction,10, 11, 12, 13, 14 specifically impaired synaptic plasticity. Consistent with the biology of neuronal p38 α , selective small molecule inhibitors of p38 α rapidly (i.e., within 2–3 weeks) reverse spatial learning defects in the APP/PS1 mouse model,15 aged rats16 and in tauopathy (hTau) mouse model 17…”
Section: Introductionmentioning
confidence: 99%
“…We have consistently found that 3 nM IL-1β significantly impairs neuronal BDNF signaling (27)(28)(29). Fig.…”
Section: Resultssupporting
confidence: 53%
“…Mossy fiber LTP is likely to be attenuated throughout the time course; therefore, we compared the EPSP 1 amplitude 30 min after HFS with that of the baseline as reported previously (3). Unlike SC-CA1 pathways, IL-1β (1 ng/mL) applied for 30 min did not affect mossy fiber LTP (155.0 ± 15.6% vs. that 1 ng/mL IL-1β was sufficient to act pathologically even though the synaptic concentrations of neurotransmitters and neuromodulators might be much higher than extracellular levels (29). The mechanisms by which IL-1β impairs hippocampal LTP remain to be fully elucidated (14).…”
Section: Resultsmentioning
confidence: 93%
“…However, some reports using primary cultured hippocampal neurons indicated that IL-1β increased NMDA-mediated Ca 2+ current (31,32); therefore, the effects of IL-1β on NMDA receptors need to be further studied. In addition to the effects on NMDA receptors, IL-1β also affects brain-derived neurotrophic factor-induced signaling in a p38-dependent manner (29), suggesting that various IL-1β-induced signaling events affect LTP induction. It is important to consider some limitations when interpreting our results.…”
Section: Referencesmentioning
confidence: 99%